Efficacy of five 'sporicidal' surface disinfectants against Clostridioides difficile spores in suspension tests and 4-field tests. (April 2022) - Gemein, S.; Andrich, R.; Christiansen, B.; Decius, M.; Exner, M.; Hunsinger, B.; Imenova, E.; Kampf, G.; Koburger-Janssen, T.; Konrat, K.; Martiny, H.; Meckel, M.; et al.
Summary: Background: A sporicidal surface disinfection is recommended both for the outbreak and the endemic setting but a comparative evaluation on the efficacy of 'sporicidal' surface disinfectants using suspension tests and 4-field tests has not been performed. Aim: To determine the efficacy of five 'sporicidal' surface disinfectants (three ready-to-use wipes (A, B, E), two concentrates (C, D) based on peroxides or aldehydes against C. difficile spores. Methods: The efficacy was determined under clean conditions using a suspension test and the 4-field test. Each test was performed in duplicate in two separate laboratories. Wipes were wrung to collect the solution for the suspension tests. Results: Product A (peracetic acid; 5 min), product C (peracetic acid; 2% solution in 15 min or 1% solution in 30 min) and product D (peracetic acid; only 2% solution in 15 min) were effective with at least a 4 log10 -reduction of C. difficile spores in suspension and on surfaces. Product B (hydrogen peroxide) was not effective in suspension (0.9 log10 after 15 min; 3.2 log10 after 1 h) and on surfaces (2.8 log10 after 15 and 60 min). Product E based on glutaraldehyde, (ethylendioxy)dimethanol and DDAC demonstrated 0.9 log10 after 4 h in suspension and 4.5 log10 after 4 h on surfaces. Conclusions: Not all surface disinfectants with a sporicidal claim were effective against C. difficile spores in standardized suspension tests and in the 4-field test. In clinical practice preference should be given to products that reliably pass the efficacy criteria of both types of tests.